Biological responses of sharks to ocean acidification. (31st March 2017) - Rosa, Rui; Rummer, Jodie L.; Munday, Philip L.
Abstract : Sharks play a key role in the structure of marine food webs, but are facing major threats due to overfishing and habitat degradation. Although sharks are also assumed to be at relatively high risk from climate change due to a low intrinsic rate of population growth and slow rates of evolution, ocean acidification (OA) has not, until recently, been considered a direct threat. New studies have been evaluating the potential effects of end-of-century elevated CO2 levels on sharks and their relatives' early development, physiology and behaviour. Here, we review those findings and use a meta-analysis approach to quantify the overall direction and magnitude of biological responses to OA in the species of sharks that have been investigated to date. While embryo survival and development time are mostly unaffected by elevated CO2, there are clear effects on body condition, growth, aerobic potential and behaviour (e.g. lateralization, hunting and prey detection). Furthermore, studies to date suggest that the effects of OA could be as substantial as those due to warming in some species. A major limitation is that all past studies have involved relatively sedentary, benthic sharks that are capable of buccal ventilation—no studies have investigated pelagic sharks that depend on ram ventilation. Future research should focus on species with different life strategies (e.g. pelagic, ram ventilators), climate zones (e.g. polar regions), habitats (e.g. open ocean), and distinct phases of ontogeny in order to fully predict how OA and climate change will impact higher-order predators and therefore marine ecosystem dynamics.